Dragon hunt - "Cowley, Joy" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Sir Brian Flockart is a gentle knight who doesn't like wearing armour and fighting battles. He also doesn't like hunting dragons. When the boastful knight Sir Roger Duckbury sets out on a dragon hunt, Sir Brian has to help his friend Meg, the dairymaid, protect their pet dragon, Grund. Or Grund might be mistaken for a dragon whose eyes turn people to stone and whose fiery breath cooks them alive..
Donated by "Book Planet", Dated 18-4-2025.
Keywords: knighthood Juvenile fiction